Progress on the Application of Modified Anode Materials for Aqueous Zinc Ion Batteries - Shao, Aiquan; Zhang, Wenhao; Liu, Jiangyong; Lv, Ke; Miao, Qinpang; Zhang, Ran; Song, Ming (International Journal of Materials Science and Technology Studies, 2024)
In the current developed electrochemical energy storage device system, drainage zinc ion batteries have attracted wide attention due to their safe operation, environmental friendliness and high theoretical specific capacity. However, when applied to the anode of drainage zinc ion batteries, uneven zinc deposition leads to the formation and growth of zinc dendrite, piercing the diaphragm and causing a short circuit in the battery. Zinc dendrites have mechanical rigidity and structural inhomogeneity, which is easy to fall off from the zinc negative electrode to form "dead zinc", leading to the reduction of active materials and the decline of battery capacity. In addition, hydrogen evolution reaction (HER), corrosion, passivation and other side reactions also occur, resulting in the stability of the battery. These adverse electrochemical reactions all occur at the zinc metal anode / electrolyte interface, which limits the development and application of drainage zinc ion battery. This paper summarizes the current carbon materials in stabilizing zinc metal anode and constructing some composite coatings to functionalize the surface of zinc anode to inhibit zinc dendrites and related side reactions, improve the stability of zinc metal anode, and then improve the electrochemical performance of drainage zinc ion battery.